Islamophobia and Misconception : A Systematic Literature Review - Cepi Novia Tristantri; M Syaprin Zahidi; Salahudin Salahudin (Journal of Islamic World and Politics, 2022)
This research aims to determine the development of the phenomenon of Islamophobia and misconceptions about Islam and Muslims that occur in the world. The research method used is a systematic literature review (SLR) using 580 scientific journal articles from the Scopus database. The article analysis uses RIS Scopus data which is visualized using the Vos Viewer application to determine the co-occurrence of the article data obtained. From the analysis carried out, the results reveal that the study of Islamophobia and Misconceptions has long been a concern of scholars/researchers. This is evidenced by the many relevant topics and sub-themes that